Rapid formation of multicellular spheroids in double-emulsion droplets with controllable microenvironment - Chan, Hon Fai; Zhang, Ying; Ho, Yi-Ping; Chiu, Ya-Ling; Jung, Youngmee; Leong, Kam W. (NATURE PUBLISHING GROUP, 2013)
An attractive option for tissue engineering is to use of multicellular spheroids as microtissues, particularly with stem cell spheroids. Conventional approaches of fabricating spheroids suffer from low throughput and polydispersity in size, and fail to supplement cues from extracellular matrix (ECM) for enhanced differentiation. In this study, we report the application of microfluidics-generated water-in-oil-in-water (w/o/w) double-emulsion (DE) droplets as pico-liter sized bioreactor for rapid cell assembly and well-controlled microenvironment for spheroid culture. Cells aggregated to form size-controllable (30-80 mu m) spheroids in DE droplets within 150 min and could be retrieved via a droplet-releasing agent. Moreover, precursor hydrogel solution can be adopted as the inner phase to produce spheroid-encapsulated microgels after spheroid formation. As an example, the encapsulation of human mesenchymal stem cells (hMSC) spheroids in alginate and alginate-arginine-glycine-aspartic acid (-RGD) microgel was demonstrated, with enhanced osteogenic differentiation further exhibited in the latter case.
Keywords: EMBRYOID BODY FORMATION; STEM-CELLS; HEPATOCYTE SPHEROIDS; MICROFLUIDIC SYSTEM; DIFFERENTIATION; CULTURE; SCAFFOLD; SIZE; MICROTISSUES; HYDROGELS